Social skills and mental health disorders - R. Pereira, Juan (2010)
This article is structured into four parts and analyzes the concept of social skills, a booming notion within the so-called Positive Psychology. First of all, this new notion will be defined.  Then, the relationship between social skills deficit and mental health disorders will be explored, as well as the relationship between social competence and health. Finally, in the last two parts, the existing association between social skills and two concrete processes - resilience and social success - will be analyzed.